LAYANAN BIMBINGAN BELAJAR BAGI SISWA YANG MENGALAMI GANGGUAN BELAJAR PADA SISWA TINGKAT SEKOLAH DASAR - Toni Elmansyah; Riki Maulana (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
Elementary school students' learning disorders are a problem that must be addressed immediately. Bearing in mind that the development of elementary school level students is characterized by the ability to make sense of what they read, being able to rewrite it, and spelling. Children will usually begin to read fluently at the age of 6 to 7 years when they are in elementary school, first and second grade. However, the facts fieldwork shows that there is a small portion of students in first and second grade elementary schools who are not yet able to read fluently and some even do not yet know letters. Of course, this is a question for teachers and parents regarding this method of learning, and it turns out that this condition is Disturbances experienced by children when learning. The aim of this research is to help children who choose dyslexic learning groups, apply the Fernald method to children with dyslexia, and change dyslexic children using the Fernald method. The method used in this research is Single Subject Research (SSR), using the A-B-A research design, there is repetition. base line phase or condition, which describes two conditions, namely before the intervention is given and after the intervention. Based on the research results, the Fernald method is suitable for students who experience dyslexia. Judging from the results before the intervention and after the intervention